Wordwall.net: Developing the 7th Grade Students’ Reading Comprehension - Mutiarani, Mutiarani; Putri, Dhaifina Az-Zahra (Journal of Foreign Language Teaching and Learning, 2024)
Reading comprehension is a topic vastly studied in the field of language learning. With the rapid development of digital technology, more focus on digital tools regarding reading comprehension is deemed necessary to find the best tool to aid its improvement. This study aimed to discover how the wordwall.net website affected seventh-grade students' reading comprehension in a descriptive text learning topic at SMP Al Amanah South Tangerang. The current quantitative study used a pre-experimental design. Twenty-eight students of class VII C were the sample for this investigation. The pre and post-tests serve as data-collecting tools. Using the t-test formula, the researcher examines how student test scores differ both before and after the treatment is applied. The paired sample t-test table shows the t count is 10.726, and the critical t at the significant level (p) = 0.05 is 1.703. Considering these results, the alternative hypothesis (Ha) is conceded. A significant effect of using the wordwall.net website for reading comprehension in grade 7 at SMP Al-Amanah has been found. The study shows that wordwall.net and other similar sites can be very helpful in making learning more fun and interactive, leading to better grades for students.